Enhancing Nurses’ Disaster Management and Preparedness: Evaluating the Effectiveness of an Online Educational Program Through a Quasi-Experimental Study - AlOtaibi SS; Almutairi HA; Alotaibi MK; Alharbi K; Bahari G (Dove Medical Press, 2024)
Sarah Saad AlOtaibi,1 Hessa Abdulrahman Almutairi,2 Mutlaq Khalid Alotaibi,3 Kholoud Alharbi,4 Ghareeb Bahari4 1Nursing Improvement Administration Department at King Saud Medical City, Riyadh, Saudi Arabia; 2Nursing Department at General Directorate of Health Affairs, Riyadh, Saudi Arabia; 3Nursing Administration Department at Afif General Hospital, Afif, Saudi Arabia; 4Administration and Education Department, College of Nursing at King Saud University, Riyadh, Saudi ArabiaCorrespondence: Ghareeb Bahari, P.O. Box 642, Riyadh, 11421, Saudi Arabia, Tel +966118054381, Email gbahari@ksu.edu.saBackground: Disaster management is an ongoing international concern, and nurses play essential roles in minimizing negative impacts on the health of communities. However, many nurses have limited knowledge and skills on how to respond to disasters effectively. Therefore, this study was conducted to determine the effectiveness of a newly developed educational program on improving nurses' disaster management and preparedness.Methods and Design: A quasi-experimental study was conducted on 88 nurses working at a public hospital. The educational program included six modules covering various aspects of disaster management. Pre-and post-tests were administered to evaluate changes in perceptions of disaster management competencies. Independent sample t-test, Pearson coefficient correlation, and One-way ANOVA tests were all run using SPSS.Results: A significant proportion of nurses (78.4%) reported ongoing training in disaster management, while a smaller percentage (21.6%) expressed a contrary opinion. Nurses also had a moderate level of agreement with the disaster preparedness program (Pretest: 2.26 ± 0.34; post-test: 2.29 ± 0.31). Further, the results showed small improvements in nursing perceptions of the operational plan after the educational program (Pretest: M=2.76, SD=0.63; Post-test: M=2.89, SD=0.44), although the differences between pre-and-post assessments were not significant (P > 0.05). The mean values for overall familiarity in the pre-test were 3.16 ± 1.39, while in the post-test, they slightly increased to 3.26 ± 1.18. The findings also showed no statistically significant differences reported in nurses' attitudes and familiarity towards disaster preparedness based on the gender, marital status, nationality, working shifts, and working hours variables (P > 0.05).Conclusion: This study demonstrated the significance of providing nurses with the essential knowledge that helps respond to disasters. Online educational programs can help improve nurses' preparedness to better manage disasters. Future research should investigate additional variables that could enhance nurses' knowledge and skills related to disaster response.Keywords: disaster management, preparedness, educational program, healthcare, nurses